Linking Academic Learning and Student Organizations to Character Development: A Study of Self-Growth among University Entrepreneurship Students - Tibrisi, A. Siti Aisyah; Dewantara, Hajar; Saharuddin, Saharuddin; Nur, Ilham (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study examines the influence of academic learning and student organizational involvement on self-growth and character development among first-year students of the Entrepreneurship Study Program at the Faculty of Economics and Business, Universitas Negeri Makassar. Conducted through a comprehensive quantitative approach, the research involved a total of 142 new students, with 67 selected as respondents using probability sampling to ensure accurate population representation. Data were systematically collected using a structured questionnaire. The study adopts a modern entrepreneurship theoretical framework that integrates character development, academic learning, and student organizational dynamics. The findings reveal a significant positive relationship between academic learning and self-growth in shaping entrepreneurial character. Academic learning emerged as the dominant factor contributing to the development of students' entrepreneurial traits. These results emphasize the importance of integrative strategies that align academic curricula, student activities, and personal development programs to foster competitive and adaptive entrepreneurial character. Theoretically, the study contributes to the advancement of sustainable entrepreneurship education by uncovering the complex mechanisms of character formation in higher education. Practically, the findings offer valuable insights for universities in designing effective curricula, mentorship programs, and talent development strategies tailored to entrepreneurship students. This research highlights the need for a multidimensional approach to character building that continuously addresses academic, organizational, and personal growth aspects.